Cell‐Permeable Peptides Containing Cycloalanine Residues. (16th August 2016) - Wu, Hao; Mousseau, Guillaume; Mediouni, Sonia; Valente, Susana T.; Kodadek, Thomas
Abstract: We present here an efficient alternative to N‐methylation for the purpose of morphing protein‐binding peptides into more serum‐stable and cell‐permeable compounds. This involves the incorporation of a cycloalanine (CyAla) into a peptide in a way that avoids difficult coupling steps. We demonstrate the utility of this chemistry in creating a cell‐permeable derivative of a high‐affinity HIV Rev protein‐binding peptide.